Analysis of the vaginal microbiome of giant pandas using metagenomics sequencing. Issue 12 (18th November 2020) - Zhang, Lan; Li, Caiwu; Zhai, Yaru; Feng, Lan; Bai, Keke; Zhang, Zhizhong; Huang, Yan; Li, Ti; Li, Desheng; Li, Hao; Cui, Pengfei; Chen, Danyu; et al.
Abstract: In this study, a total of 14 vaginal samples (GPV1‐14) from giant pandas were analyzed. These vaginal samples were divided into two groups as per the region and age of giant pandas. All the vaginal samples were analyzed using metagenomic sequencing. As per the outcomes of metagenomic analysis, Proteobacteria (39.04%), Firmicutes (5.27%), Actinobacteria (2.94%), and Basidiomycota (2.77%) were found to be the dominant phyla in the microbiome of the vaginal samples. At the genus level, Pseudomonas (21.90%) was found to be the most dominant genus, followed by Streptococcus (3.47%), Psychrobacter (1.89%), and Proteus (1.38%). Metastats analysis of the microbial species in the vaginal samples of giant pandas from Wolong Nature Reserve, Dujiangyan and Ningbo Youngor Zoo, and Ya'an Bifengxia Nature Reserve was found to be significantly different ( p < 0.05). Age groups, that is, AGE1 (5‐10 years old) and AGE2 (11‐16 years old), also demonstrated significantly different inter‐group microbial species ( p < 0.05). For the first time, Chlamydia and Neisseria gonorrhoeae were detected in giant pandas' reproductive tract. GPV3 vaginal sample (2.63%) showed highest Chlamydia content followed by GPV14 (0.91%), and GPV7 (0.62%). GPV5 vaginal sample (7.17%) showed the highest Neisseria gonorrhoeae content, followed by GPV14 (7.02%), and GPV8 (6.50%). Furthermore, we employed eggNOG, CAZy, KEGG, and NCBI databases to investigate the functional significance of giant panda's vaginal microbial community. The outcomes indicated that giant panda's vaginal microbes were involved in biological processes. The data from this study will help in improving the reproductive health of giant pandas. Abstract : In this study, metagenomic sequencing methods were used to analyze the vaginal microbial population structure and gene functional activity in giant pandas. Significant differences were found in the different components of the microbiota in the reproductive tract, and they may be related to the regional and age differences. The main microbial pathways and carbohydrate‐active enzymes also varied with giant pandas' age and region.